Scintillation Proximity Assay to Detect the Changes in Cellular Dihydrosphingosine 1‐Phosphate Levels. Issue 10 (2nd September 2016) - Ohtoyo, Mamoru; Tamura, Masakazu; Machinaga, Nobuo; Muro, Fumihito; Hashimoto, Ryuji
Abstract: Compounds that modulate the activity of sphingosine 1‐phosphate (S1P)‐metabolizing enzymes are expected to be potential therapeutic agents for various diseases. Investigation of their potencies requires not only cell‐free but also cell‐based assays in which intracellular accumulation/depletion of S1P could be monitored. However, conventional methods have limitations to their simplicity, mainly due to the necessity of a separation process that separates S1P from its related substances. Here, we describe a method utilizing a scintillation proximity assay (SPA) for semi‐quantifying intracellular [ 3 H]‐labeled dihydroS1P ([ 3 H]dhS1P), which is also a substrate for S1P‐metabolizing enzymes. We found that uncoated yttrium silicate SPA beads could selectively bind to and detect [ 3 H]dhS1P rather than [ 3 H]dihydrosphingosine (the non‐phosphorylated form of [ 3 H]dhS1P). Based on this, we developed a novel cell‐based assay system which does not require any organic solvent extraction or chromatographic separation, and confirmed its practicality by using siRNA targeting S1P lyase (S1PL) and known S1PL inhibitors as models. Our results demonstrated that this assay is useful for rapid and easy evaluation of S1PL inhibitors, and could be potentially applicable for all compounds that modulate the activity of S1P‐metabolizing enzymes.